STUDI KOMPARASI KRITERIA AWAL BULAN KAMARIAH KALENDER FAZILET DAN KRITERIA MABIMS - Anwar., Irfan.; Mahyuddin Latuconsina (ELFALAKY: Jurnal Ilmu Falak, 2023)
A calendar is an organizing system for calculating time over a certain period. Some calendar systems refer to an astronomical cycle, following a fixed rule. The main problem in this study is how the method and implementation of determining the beginning of the lunar month in the Ministry of Religion of the Republic of Indonesia and the Fazilet Calendar, the purpose of this study is to add to the treasury of knowledge about the Fazilet Calendar calendar method originating from the Ottoman Empire so that library research methods are used to describe various sources that are there is. The results showed that there was a difference of three to four months each year in entering the first month using the old and new MABIMS criteria and the Fazilet Calendar criteria. Differences in the beginning of the lunar month also occur because of the location of the hilal observation markaz, the Fazilet Calendar with the Ittihadul Mathali concept (imposing a global matla) while the Ministry of Religion of the Republic of Indonesia with the wilayatul hukmi matlak concept.